Reducing Sugar Production by Cellulose Immobilized Enzyme from the Oil Palm Empty Fruit Brunch (OPEFB) Treated by Organosolv Pretreatment - Pardeny, Vini Ivania; Nurfadiya, Alvanissa; Hidayatulloh, Irwan; Haq, Muhammad Umair Ul; Permanasari, Ayu Ratna (Jurnal Teknik Kimia dan Lingkungan, 2023)
Oil Palm Empty Fruit Bunches (OPEFB) is lignocellulosic that consists of 13.20-25.31% lignin, 42.70-65.00% cellulose, and 17.10-33.50% hemicellulose. Cellulose can be used as a material for a new renewable energy source in the term of reducing sugar through a combination of organosolv pretreatment and hydrolysis process using immobilized enzymes. Organosolv pretreatment was used for lignin degradation, by using ethanol as solvent, which are environmentally friendly and easy to recover, with a concentration S/L 10%(w/w), in 160°C for 90-150 min. The following process is to produce crude enzyme from Aspergillus niger and Trichoderma viride. The resulting crude enzyme cellulase activity of 0.774 U/mL. Then, the crude enzyme is immobilized by Chitosan-GDA. OPEFB hydrolysis process with immobilized cellulase was carried out for 5, 7 and 9 days at 37°C. The best result of lignin degradation reaches out 56.68% lignin removal at 160°C for 150 min, while the hydrolysis of cellulose gives the highest yield, 47.59%, in the 9 days processing time.